(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
In the world, much attention is paid to protecting the environment from pollution and solving environmental problems. First of all, harmful substances emitted by transport cause great harm to plants. Tree leaves are one of the main vegetative organs of plants and perform the functions of photosynthesis, transparency and gas exchange. Harmful substances emitted by vehicles adversely affect the leaves of ornamental trees. Leaves and plant cells that absorb nitrogen oxides from the air begin to die. The amount of pigments in the leaves of a tree acts as an indicator that determines the state of a particular environment.